Modafinil Dependence and Hypersexuality: A Case Report and Review of the Evidence - Swapnajeet, Sahoo (Clin Psychopharmacol Neurosci, 2016)
Apart from sleep wake disorders, nowadays, modafinil is being prescribed for several psychiatric disorders including depression. Despite being reported as to be having very low abuse potential, cases of modafinil dependence had come to the limelight. In this case report, we describe a 35 year old man with bipolar affective disorder while in remission who developed modafinil dependence and later on, had hypersexuality when he increased the dose of modafinil from 400 to 1,000 mg/day. Existing literature suggests that modafinil when taken above prescribed doses can cause many side effects ranging from nausea, vomiting to psychotic exacerbation and mania. However, hypersexuality as a side effect of modafinil overuse is not commonly seen. The exact pathophysiological mechanism of modafinil induced hypersexuality is not clear. Clinicians should be aware of possibility of modafinil leading to dependence and this rare significant side effect of modafinil.